Pengaruh Embung Mini Terhadap Produktivitas Tanaman Kakao (Theobroma Cacao L.) Dengan Pemberian Pupuk Organik Kotoran Kambing Dan Poc Urin Kambing - Suciati; Sunaryo, Yacobus; Susilaningsih, Sri Endah Prasetiowati (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to determine the response of the use of mini ponds to the productivity of cocoa plants by providing organic fertilizer of goat manure and POC of goat urine and to determine the response of the control treatment without the use of mini ponds on the productivity of cocoa plants. This experiment was carried out in Widoro Hamlet, Bunder Village, Patuk District, Gunung Kidul Regency, Special Region of Yogyakarta. The altitude is 550 m above sea level (asl), the type of soil is gromosol, with a soil pH of 5.5-6.7, the average temperature is 22o C-31oC, and the rainfall is 1,564.00 mm/year. This research was conducted in the form of a completely randomized design (CRD) with five treatments, namely treatment T0 control without ponds, Treatment T1: Goat dung fertilizer was directly given to the tree and POC was directly given to the tree, Treatment T2: Goat dung fertilizer was directly given to the tree and POC Treatment is given directly to the pond, Treatment T3: goat manure is directly applied to the pond and POC is directly given to the trees, Treatment T4: goat manure is directly given to the pond and POC is directly given to the pond and each treatment is repeated five times. Analysis of the results of observations using a 5% level of variance followed by the Duncan's Multiple Range Test (DMRT) distance test at a level of = 5%. The results showed that the use of mini ponds and the application of goat manure and goat urine POC had no significant effect on crown height, number of branches, leaf width, number of flower buds, number of nipples, number of nipple wilts, number of harvested fruits, number of large fruits, number of fruits. small size, number of diseased fruit, weight of harvested fruit, weight of skin, weight of fresh seeds and weight of dry seeds. However, the use of mini ponds and the application of goat manure and goat urine POC had a significant effect on stem circumference, leaf length and light intensity.